Data sharing platforms and the academic evaluation system. (12th July 2020) - Devriendt, Thijs; Shabani, Mahsa; Borry, Pascal
Abstract : Data‐level metrics could encourage scientists to openly share data – a goal of Open Science – if these DLMs became part of the academic reward system.